Changes over time in head and neck cancer patients' and caregivers' illness perceptions and relationships with quality of life. Issue 10 (2nd October 2016) - Richardson, Amy E.; Morton, Randall P.; Broadbent, Elizabeth A.
Abstract : Objective: This study investigated changes in illness perceptions from diagnosis to six months later in patients with head and neck cancer (HNC) and their caregivers. The study also examined whether discrepancy in patient and caregiver perceptions at diagnosis predicted patient health-related quality of life (HRQL) at six months. Design: Forty-two patient–caregiver dyads completed the Brief Illness Perception Questionnaire (Brief IPQ) at diagnosis and again six months later. Patients also completed a HRQL questionnaire at both time points. Analyses were performed using the Actor–Partner Interdependence Model. Main Outcome Measure: Total patient HRQL assessed by the Functional Assessment of Cancer Therapy (FACT-H&N). Results: Perceptions of emotional impact and illness concern reduced over time in patients and caregivers. Perceptions of treatment control and identity increased in caregivers only. After controlling for the effects of baseline HRQL, and the individual contribution of patient and caregiver illness perceptions, greater discrepancy in perceptions of timeline, personal control, and illness identity among dyads at diagnosis predicted lower patient HRQL at six-month follow-up. Conclusion: Patients' and their caregivers' perceptions of HNC are dynamic over time. Greater discrepancy between patients' and caregivers' illness perceptions at diagnosis predict poorer subsequent patient HRQL.